Enhanced nicotine self‐administration and suppressed dopaminergic systems in a rat model of diabetes. (8th July 2013) - O'Dell, Laura E.; Natividad, Luis A.; Pipkin, Joseph A.; Roman, Francisco; Torres, Ivan; Jurado, Jesus; Torres, Oscar V.; Friedman, Theodore C.; Tenayuca, John M.; Nazarian, Arbi
Abstract Patients with diabetes display a heightened propensity to use tobacco; however, it is unclear whether they experience enhanced rewarding effects of nicotine. Thus, this study examined the reinforcing effects of nicotine in a rodent model of diabetes involving administration of streptozotocin (STZ), a drug that is toxic to pancreatic insulin‐producing cells. The first study compared STZ‐ and vehicle‐treated rats that had 23‐hour access to intravenous self‐administration (IVSA) of nicotine or saline and concomitant access to food and water. In order to examine the contribution of dopamine to our behavioral effects, dopamine transporter (DAT), D1 and D2 receptor levels were compared in the nucleus accumbens (NAc) following 10 days of nicotine or saline IVSA. Dopamine levels in the NAc were also compared following nicotine administration. Lastly, nicotine metabolism and dose‐dependent effects of nicotine IVSA were assessed. The results revealed that STZ‐treated rats displayed enhanced nicotine intake and a robust increase in food and water intake relative to controls. Protein analysis revealed an increase in DAT and a decrease in D1 receptor levels in the NAc of STZ‐ versus vehicle‐treated rats regardless of IVSA condition. STZ‐treated rats also displayed suppressed NAc dopamine levels during baseline and in response to nicotine. STZ treatment did not alter our assessment of nicotine metabolism. Furthermore, STZ treatment increased nicotine IVSA in a dose‐dependent manner. Our findings suggest that STZ‐treatment increased the rewarding effects of nicotine. This suggests that strong reinforcing effects of nicotine may contribute to greater tobacco use in patients with diabetes.